IgG4-related disease: a review with an Indian perspective - Duggal, Lalit; Jain, Neeraj; Singh, Bhandari Gurbir; Patel, Jeet Hemant Kumar; Goyal, Vishal; Gupta, Disha (International Journal of Research in Medical Sciences, 2021)
IgG4-related disease (IgG4-RD) is a recently discovered (2003) complex disease, manifesting in various organs with symptoms mimicking other diseases. Progression of the disease leads to organ failure and hence early diagnosis is an urgent requirement in these patients. There is scarcity in reporting of IgG4-RD globally and in India. The aim of the study was to generate awareness on the epidemiology, diagnosis, and practice trends for IgG4-RD in India and globally, and to aid Indian physicians in early diagnosis of IgG4-RD in patients. Additionally, the evidence currently available in the Indian subpopulation has been evaluated. A preliminary literature search was performed using the PubMed database with the keywords including ‘IgG4-related disease’ in the title and abstract to obtain the relevant data. In total, PubMed identified 2071 publications comprising world-wide studies published in the English language before 30 April 2021. Studies were filtered region-wise by adding ‘India’ to the search strategy and total 60 publications were identified. The relative newness of IgG4-RD and the ensuing paucity in literature limits diagnosis by clinicians. Awareness of the disease among Indian clinicians would improve understanding of the disease and development of a country-specific consensus-based management guideline might lead to better prognosis in Indian patients with IgG4-RD.